Principal Leadership and Learning Quality in Elementary Schools: A Quantitative Analysis of Multidimensional Leadership Effects in Indonesian Rural Context - Yatini Yatini; Supandi Supandi; Nurkolis Nurkolis (Papanda Publisher, 2026)
Principal leadership plays a crucial role in creating conducive learning environments, yet significant variations in learning quality across elementary schools suggest inadequate understanding of leadership mechanisms in specific contexts. This quantitative study employed correlational survey design to examine principal leadership effects on learning quality in 26 public elementary schools in Tanggungharjo District, Indonesia. Data were collected from 137 teachers using validated questionnaires measuring five leadership dimensions (personality, managerial competence, academic supervision, social communication, and entrepreneurship/innovation) and learning quality indicators. Principal Component Analysis assessed dimensional structure, while Pearson correlation and simple linear regression analyzed variable relationships. Principal leadership demonstrated very strong positive correlation with learning quality (r = 0.893, p < 0.01), explaining 79.7% of learning quality variance. Dimensional analysis revealed academic supervision and entrepreneurship/innovation as strongest contributors (extraction values = 0.996), while managerial and social-communication dimensions showed relatively lower contributions. The regression equation (Y = 29.588 + 0.596X) confirmed significant positive influence (t = 22.994, p < 0.001). Findings validate integrated transformational-instructional leadership frameworks, demonstrating that contemporary principal effectiveness requires simultaneously excelling as pedagogical supervisors and entrepreneurial innovators. Results emphasize urgent need for targeted leadership development interventions, particularly in schools where 45.99% of respondents perceived inadequate leadership quality, to strengthen academic supervision competencies and entrepreneurial mindsets for sustainable educational improvement.